Transcriptomic response of lumpfish (Cyclopterus lumpus) head kidney to viral mimic, with a focus on the interferon regulatory factor family - Emam, Mohamed; Kumar, Surendra; Eslamloo, Khalil; Caballero-Solares, Albert; Hall, Jennifer R.; Xue, Xi; Paradis, Hélène; Gendron, Robert L.; Santander, Javier; Rise, Matthew L. (Frontiers in Immunology, 2024)
The economic importance of lumpfish (Cyclopterus lumpus) is increasing, but several aspects of its immune responses are not well understood. To discover genes and mechanisms involved in the lumpfish antiviral response, fish were intraperitoneally injected with either the viral mimic polyinosinic:polycytidylic acid [poly(I:C)] or phosphate-buffered saline (PBS; vehicle control), and head kidneys were sampled 24 hours post-injection (hpi) for transcriptomic analyses. RNA sequencing (RNA-Seq) (adjusted p-value <0.05) identified 4,499 upregulated and 3,952 downregulated transcripts in the poly(I:C)-injected fish compared to the PBS-injected fish. Eighteen genes identified as differentially expressed by RNA-Seq were included in a qPCR study that confirmed the upregulation of genes encoding proteins with antiviral immune response functions (e.g., rsad2) and the downregulation of genes (e.g., jarid2b) with potential cellular process functions. In addition, transcript expression levels of 12 members of the interferon regulatory factor (IRF) family [seven of which were identified as poly(I:C)-responsive in this RNA-Seq study] were analyzed using qPCR. Levels of irf1a, irf1b, irf2, irf3, irf4b, irf7, irf8, irf9, and irf10 were significantly higher and levels of irf4a and irf5 were significantly lower in the poly(I:C)-injected fish compared to the PBS-injected fish. This research and associated new genomic resources enhance our understanding of the genes and molecular mechanisms underlying the lumpfish response to viral mimic stimulation and help identify possible therapeutic targets and biomarkers for viral infections in this species.